Effect of Thrombocytopenia in Pregnancy and Their Maternal Outcome: Thrombocytopenia and Maternal Outcome - Mukhtar, Hina; Uzma, Syeda; Ch, Sadia Zainab; Hayat, Naheed (Pakistan Journal of Health Sciences, 2025)
Gestational thrombocytopenia is a common hematological disorder during pregnancy that can significantly impact maternal health, depending on its severity. Objective: To assess the effects of thrombocytopenia severity on key maternal outcomes, including antepartum and postpartum hemorrhage, and placental abruption. Methods: In this prospective study, 192 pregnant women diagnosed with thrombocytopenia were analyzed at the Department of Obstetrics and Gynecology, Tertiary Care Hospital, Bahawalpur, from March 07, 2023, to September 06, 2023. We evaluated the severity of thrombocytopenia, maternal age, platelet count, and gestational age, examining their associations with maternal health outcomes using chi-square and correlation analysis. Results: No significant correlation was found between thrombocytopenia severity and maternal age (p=0.467). Severe thrombocytopenia was strongly associated with increased risks of antepartum hemorrhage (100% of cases), postpartum hemorrhage, and placental abruption (p<0.001 for both). Additionally, a moderate positive correlation was observed between platelet count and gestational age (r=0.478, p<0.001), indicating a potential link between the progression of pregnancy and changes in thrombocytopenia severity. Conclusions: It was concluded that severe gestational thrombocytopenia markedly increases maternal risks, underscoring the importance of diligent monitoring and management. The findings advocate for early detection and proactive interventions to enhance maternal outcomes in thrombocytopenic pregnancies.